PENGARUH PARTISIPASI MASYARAKAT TERHADAP KUALITAS PENGELOLAAN KEUANGAN DESA (Studi Kasus Pada Desa Kecamatan Tanjung Kemuning) - dwi sukma, anggri (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2023)
The title of this research is Community Participation in the Quality of Village Financial Management (Case Study of a Village in Sungai Rumbai District). This research aims to prove the influence of community participation on the quality of village financial management (case study in the village of Tanjung Kemuning District). Sampling in this research was by using a proportional sampling technique, namely the number of respondents used in this research was 57 respondents. To more efficiently obtain data from respondents, researchers used questionnaire data. The data analysis technique used is a countable analysis technique or data in the form of numbers and calculations using statistical methods, then the data must be classified into certain categories using tables to make it easier to analyze using the SPSS (Statistical Package for Social Sciences) program. The results of the hypothesis test show that the Community Participation Variable has a positive and significant effect on the Quality of Village Financial Management with a calculated t result of 7.640> t table 2.004 with a significance level of 0.000 <0.05. Then the adjusted coefficient of determination (Adjusted R Square) of 0.506 means that the variation that occurs in variable Y (Quality of Village Financial Management) is 50.6% determined by the variable Level of Community Participation. Keywords: Community Participation and Quality of Village Financial Management